Rethinking Women’s Return Migration: Evidence from Tunisia and Morocco - Stellamarina Donato; Consuelo Corradi; Umberto Di Maggio (Societies, 2025)
Return migration is frequently associated with failure, particularly in the context of women returnees from the global south. This research challenges this notion, focusing on women returnees from Italy to North Africa. It aims to analyze return migration by focusing on women who returned to Morocco and Tunisia in the last 15 years, and the aftermath of the Arab uprisings, emphasizing the transformative potential of migration experiences for themselves and the local community. Women returnees not only redefine their roles in society but also foster socio-economic development, community building, and political changes in the countries of return. The study employs thematic analysis to examine 25 semi-structured interviews conducted with returnees aged 25–60, where women shared insights into their migration, re-adaptation experiences, and challenges upon return. Returnees utilized skills gained abroad to achieve economic empowerment, often starting businesses or finding new jobs. However, they faced cultural challenges, particularly societal expectations of traditional gender roles. Nonetheless, migration empowered many returnees to question these policies and norms, and contribute to societal change.